Association Between Social Support and Job Satisfaction Among Mainland Chinese Ethnic Minority Kindergarten Teachers: The Mediation of Self-Efficacy and Work Engagement - Wu, Shiyong; Zhou, Shuyi; Yu, Xiaoyan; Chen, Wei; Zheng, Wen; Huang, Mingxi; Zhang, Hongbao; Li, Xiujuan; Fang, Guangbao; Zhao, Xiaowei; Zhang, Kai (Frontiers in Psychology, 2020)
Grounded on the social exchange theory (SET), social cognitive theory (SCT), and self-determination theory (SDT), this study aims to explore the mediating role of self-efficacy (SE) and work engagement (WE) on the effect of social support (SS) on job satisfaction (JS) among Chinese ethnic minority kindergarten teachers (KTs). The results show that: (1) SS has a directly significant effect on JS; (2) WE mediates the relationship between SS and JS; and (3) SE mediates the relationship between SS and WE. Although the mediation of SE on the relationship between SS and JS is not found, the posited multiple mediations of SE and WE on the relationship between SS and JS are totally accepted. The results reveal that SS mainland Chinese ethnic minority KTs received can not only have a direct effect on JS but also have an indirect impact through the one-path mediating role of WE and the chain mediating role of SE and WE. The results suggest that governments, supervisors, and sponsors should work together to provide ethnic minority KTs with more prioritized SS from both cultural psychology and financial material and opportunities for facilitating professional knowledge and skills in order to enhance their SE, inspire their WE, and eventually accumulate their JS.